The design of vertical R&D collaborations - Patrick Herbst; Uwe Walz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
Suppliers play a major role in innovation processes. We analyze ownership allocations and the choice of R&D technology in vertical R&D cooperations. Given incomplete contracts on the R&D outcome, there is a tradeoff between R&D specifically designed towards a manufacturer (increasing investment productivity) and a general technology (hold-up reduction). We find that the market solution yields the specific technology in too few cases. More intense product market competition shifts optimal ownership towards the supplier. The use of exit clauses increases the gains from the collaboration.
urn:nbn:de:hebis:30-63776
Keywords: L22; L24; O31; O32; 330; Managing Innovations; Vertical R&D; R&D Collaboration; Rent-Seeking; Forschungskooperation; Industrielle Forschung; Lieferanten-Kunden-Beziehung; Innovationsmanagement; Eigentümerstruktur; Rent Seeking; Unvollständiger Vertrag; Theorie